The wild grape genome sequence provides insights into the transition from dioecy to hermaphroditism during grape domestication - Badouin, Hélène; Velt, Amandine; Gindraud, François; Flutre, Timothée; Dumas, Vincent; Vautrin, Sonia; Marande, William; Corbi, Jonathan; Sallet, Erika; Ganofsky, Jérémy; Santoni, Sylvain; Guyot, Dominique; et al. (Genome Biology, 2020)
Background A key step in domestication of the grapevine was the transition from separate sexes (dioecy) in wild Vitis vinifera ssp. sylvestris (V. sylvestris) to hermaphroditism in cultivated Vitis vinifera ssp. sativa (V. vinifera). It is known that V. sylvestris has an XY system and V. vinifera a modified Y haplotype (Yh) and that the sex locus is small, but it has not previously been precisely characterized. Results We generate a high-quality de novo reference genome for V. sylvestris, onto which we map whole-genome re-sequencing data of a cross to locate the sex locus. Assembly of the full X, Y, and Yh haplotypes of V. sylvestris and V. vinifera sex locus and examining their gene content and expression profiles during flower development in wild and cultivated accessions show that truncation and deletion of tapetum and pollen development genes on the X haplotype likely causes male sterility, while the upregulation of a Y allele of a cytokinin regulator (APRT3) may cause female sterility. The downregulation of this cytokinin regulator in the Yh haplotype may be sufficient to trigger reversal to hermaphroditism. Molecular dating of X and Y haplotypes is consistent with the sex locus being as old as the Vitis genus, but the mechanism by which recombination was suppressed remains undetermined. Conclusions We describe the genomic and evolutionary characterization of the sex locus of cultivated and wild grapevine, providing a coherent model of sex determination in the latter and for transition from dioecy to hermaphroditism during domestication.